2009
DOI: 10.1016/j.cryobiol.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental cryosurgery investigations in vivo

Abstract: Cryosurgery is the use of freezing temperatures to elicit an ablative response in a targeted tissue. This review provides a global overview of experimentation in vivo which has been the basis of advancement of this widely applied therapeutic option. The cellular and tissue-related events that underlie the mechanisms of destruction, including direct cell injury (cryolysis), vascular stasis, apoptosis and necrosis, are described and are related to the optimal methods of technique of freezing to achieve efficacio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
211
0
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(239 citation statements)
references
References 198 publications
(207 reference statements)
6
211
0
14
Order By: Relevance
“…In addition, many of the surrounding structures such as the connective tissues of the nerves and blood vessels, as well as the bone, have been found to resist freeze injury [32]. The result is that the extracellular matrix and scaffold structure of the nerves and vessels remain intact, allowing the affected axon/myelin sheath or vascular cells to regenerate and repair the injury site.…”
Section: Safety Of Cryoneurolysismentioning
confidence: 96%
“…In addition, many of the surrounding structures such as the connective tissues of the nerves and blood vessels, as well as the bone, have been found to resist freeze injury [32]. The result is that the extracellular matrix and scaffold structure of the nerves and vessels remain intact, allowing the affected axon/myelin sheath or vascular cells to regenerate and repair the injury site.…”
Section: Safety Of Cryoneurolysismentioning
confidence: 96%
“…Previous reports have demonstrated that repeated exposure of cancer cells to thermal treatment results in increased cell death [18,38]. As such, thermal ablation is typically applied as a monotherapy in a repeat exposure protocol.…”
Section: Impact Of Dual Thermal Ablationmentioning
confidence: 99%
“…Further, unlike other treatment strategies, molecular drug resistance can be overcome with thermal injury [10]. Although cryoablation is not a mainstream thermal technique for PaCa, it is a primary treatment option in other cancers [6,[16][17][18][19][20][21][22]. In 2008, the American Urological Association published a best practice statement on prostate cancer, recommending cryosurgery as a primary treatment option [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, while osteocytes will definitely die in this temperature range, tissue from a healthy liver, kidney or prostate can survive one-time application of such a temperature. Compared to healthy cells, tumor cells have greater and variable resistance to cold [9]. Moreover, fibroblasts and collagen fibers usually survive a freezing process [10].…”
Section: Mechanism Of Action and Cryobiologymentioning
confidence: 99%